Secretory expression of human insulin precursor in Pichia pastoris employing truncated α-factor leader sequence and a short C-peptide - Dini Nurdiani; Hariyatun Hariyatun; Wien Kusharyoto (Indonesian Journal of Biotechnology, 2018)
In the past ten years, diabetes prevalence has increased rapidly in low- and middle-income countries due to lifestyle changes. This increased number of diabetic patients leads to the escalation of recombinant insulin demand, which is creating a large global insulin market. Pichia pastoris has appeared as an alternative host to produce recombinant proteins. It has excellent qualifications as an expression host for large-scale production of recombinant proteins for therapeutic use. In this study, we attempted to express the insulin precursor (IP) in P. pastoris. We used a synthetic IP-encoding gene constructed in frame with the truncated α-factor secretory signal and a short C-peptide (DGK) linked A- and B-chain of human insulin in a pD902 expression vector. Several zeocin resistant clones were successfully obtained and verified with PCR using AOX1 specific primers for the integration of the expression cassette into the P. pastoris genome and for the identification of Mut phenotypes. The secretion of IP by the Pichia pastoris clone in the culture supernatant was confirmed using SDS-PAGE, where a single band of the secreted IP with a molecular mass above 6.5 kDa was found.